Strategy and management in Asia Pacific - Lasserre, Philippe; Schutte, Hellmut (London : McGraw-Hill Publishing, 1999)
Business
Keywords: Strategic management; Marketing; Business marketing; Customer; Business logic; Partnership; Organization